Promoting control of antiferromagnet-induced perpendicular magnetic anisotropy in magnetic multilayers: Effects of applying in-plane magnetic supporting layers. (27th March 2019) - Wang, Bo-Yao; Huang, Chun-Wei; Tsai, Ming-Shian; Lin, Kai; Chung, Chun-Chieh; Jih, Nae-Yeou; Lu, Chun-I; Chuang, Tzu-Hung; Wei, Der-Hsin
Abstract: We report that antiferromagnet-induced perpendicular magnetic anisotropy (PMA) occurring in magnetic thin films can be effectively controlled by applying ultrathin in-plane magnetic supporting layers with high ferromagnetic ordering temperature through magnetic proximity effects. In a series of epitaxially grown 12-ML Ni/Co/Mn/Co/Cu(001) films, we observed that the PMA of the top 12-ML Ni/Co films and the long-range antiferromagnetic ordering of Mn film were enhanced concurrently with the establishment of ferromagnetic ordering of the bottom Co film. This clearly proves the underlying mechanism of magnetic proximity effects, and offers another degree of freedom for the control of perpendicular-based magnetic logical devices.